PEMBERIAN SANKSI SEBAGAI UPAYA PEMERINTAH INDONESIA DALAM PROGRAM PERCEPATAN VAKSINASI COVID-19 - Ade Oktiviyari; Febri Nurrahmi; Irwansyah Irwansyah (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2023)
In early 2019, Indonesia launched its Covid-19 vaccination program. However, this was met with controversy and widespread hoax news, resulting in increased vaccine hesitancy and lower vaccination rates. To combat this, the government implemented a penalty system for those in the target vaccination group who refused the vaccine without medical justification. These penalties included travel bans, restrictions on public services, and delayed salary payments for government employees. As the pandemic and global situation evolved, the government adjusted the regulations multiple times. Despite the controversy surrounding the penalty system, it has proven effective in increasing vaccination rates dramatically. This article reviews the impact of the penalty system on the Covid-19 vaccination program in Indonesia between 2021 and 2022. This review highlights that the effectiveness of the penalty system in increasing vaccination rates, despite its controversy.